Cytogenetics and DNA barcoding of the Round-eared bats, Tonatia (Chiroptera: Phyllostomidae): a new karyotype for Tonatia bidens - Jaqueline R. Tavares; Tatiane P. de Sousa; Joaquim M. da Silva; Paulo C. Venere; Karina de C. Faria (Zoologia (Curitiba), 2015)
ABSTRACT There are two species of Neotropical Round-eared bats, Tonatia bidens Spix, 1823 and Tonatia saurophila Koopman & Williams, 1951, which present highly similar morphological characteristics that can lead to errors of identification. Specimens originally identified as T. bidens have recently been reclassified as T. saurophila, and the only karyotype documented previously for these species was 2n = 16, FN = 20. In the present study, specimens of Tonatia collected in the municipality of Barra do Garças, in the Brazilian state of Mato Grosso, were analyzed morphologically, using conventional cytogenetic techniques (C-banding, Ag-NOR, and CMA3), and through sequences of the mitochondrial cytochrome c oxidase subunit I (COI) gene. In the specimens morphologically identified as T. bidens, the diploid number (2n) was 26, and the fundamental number (FN), 38, while in T. saurophila, 2n = 16 and FN = 20, which is the karyotype also described previously for T. bidens. The dendograms obtained with sequences of the COI marker resulted in the formation of two distinct groups between T. bidens and T. saurophila, consistent with the two species, with a high sequence divergence value (14.22%). Distinct clades were also observed between T. bidens and the other phyllostomines analyzed in this study, with T. bidens also close to Phyllostomus hastatus (14.18% of sequence divergence).